PSYCHOLOGICAL STRESS AMONG THE DRUZE TEACHERS IN ISRAEL IN AN ONLINE LEARNING ENVIRONMENT DURING COVID- 19 - Haj, Maysaa (E-Journal VFU, 2025)
This study explored the reasons that led to the emergence of psychological pressures among druze teachers in an online learning during the COVID-19 pandemic and identified the coping mechanisms of Druze teachers in managing psychological pressures during online learning. The sample of the study involved 12 Druzi teachers and principals in Israel. To analyze data, Braun and Clarke (2006) thematic approach was use. The findings of the study were : (i) Rapid learning of techniques and working longer hours drained the energy of teachers and increased their stress, (ii) The weakness of the internet hampered communication with students, increased frustration and psychological stress, (iii) Family and community ties eased psychological stress and strengthened resilience, (iv) Developing skills and communicating with colleagues helped to cope with isolation and lack of support, (v) The lack of training and support increased the pressures, while communication with management partially alleviated them. The following strategies for coping with psychological stress : Fostering support and collaboration: includes leveraging family and community ties, spiritual values, and peer-to-peer collaboration across communication platforms to relieve psychological stress and reduce isolation. Professional development and self-reliance: includes self-learning for the development of digital skills, communication with management for institutional support and alleviation of workloads.
Keywords: COVID- 19; Druze Teachers; Israel; Psychological Stress